RANCANG BANGUN APLIKASI PEMESANAN KUE BERBASIS MOBILE PADA TOKO KUE PRIMADONA - Rojiman Hadi Saputra; Moh Ali Albar; Nadiyasari Agitha (Program Studi Teknik Informatika, Fakultas Teknik, Universitas Mataram, 2020)
The development of technology affects the society in industry, either big or small scale of industry. In Mataram city, there are a lot of businesses that have utilized technology to improve their businesses. The technology usually used is smartphone. Smartphone is chosen because it’s mobility and easiness to use. Although smartphone technology has been used widely, there are some businesses which does not have information system and still use manual system in their business operation. One of them is UD. Primadona’s cake shop. Therefore it is important to assist them by designing a mobile-based order application. The method used is waterfall, which consist of several steps in its design, including analysis of system requirement, designing, implementation, testing, and maintenance. For the database, XAMPP used as a server and PHP used to connect with the mobile application that will be built by using ionic framework. The result from the black box testing shows that all features work well. Meanwhile, the questionnaire of 30 respondents reveals that mean value for all question is 3.85. hence, it can be concluded that the order application designed is good and work well. Keywords: Technology, Store, Smartphone Waterfall, Ionic, MOS.